Do we have a right to an unmanipulated genome?: The human genome as the common heritage of mankind - Primc, Nadia (Bioethics, 2020)
The human genome is commonly regarded as a ‘natural’ connection between all human beings, as it has been handed down to us by our predecessors. As such, it is believed to represent common heritage of humanity, e.g. a resource of outstanding value that should be the object of special protection and international concern. Some critics argue that germline manipulation would disrupt this natural heritage and that we have a duty to preserve the integrity of the human germline. However, a closer look reveals that the concept of common heritage of humanity does not necessarily imply the impermissibility of germline manipulation. If it is restricted to the prevention of severe diseases, germline manipulation does not represent a threat to the unity and identity of the human species, even though this would create a new form of relationship between human beings, namely that between a designer and a genetically designed person.
First published: 20 June 2019
Gesehen am 17.01.2020